The Role of Islamic Boarding Schools in Digital Literacy: Strategies to Shape a Critical and Productive Muslim Generation - Arizqi, Arizqi Ihsan Pratama; Nisa, Ulfatun Wahidatun; Abdullah, Achmad Farouq; Kurniawan, Muhammad Irfanudin (Fakultas Tarbiyah, Universitas Darussalam Gontor, 2025)
Purpose -The digital era poses both challenges and opportunities for Islamic boarding schools (pesantren) in Indonesia. This study investigates the strategic role of pesantren in fostering digital literacy to shape a generation of Muslims who are both critical and productive. The research aims to analyze how digital literacy is integrated into pesantren education and the strategies employed to align technological use with Islamic ethical values. Methods -Adopting a qualitative library research method, the study draws from a wide range of primary and secondary sources, including academic literature and documented case studies. Findings –The findings reveal several key strategies: integration of digital subjects into curricula, training and workshops for students and teachers, policy reinforcement on technology use, ethical digital education, and collaboration with external institutions. Research implications / limitations -Case studies from pesantren such as Nurul Jadid, Darunnajah, and Al-Muayyad demonstrate successful implementations through e-learning platforms, digital preaching programs, and content creation training. Despite notable challenges such as limited infrastructure, cultural resistance, and a lack of digital competence among educators the study affirms the potential of pesantren to serve as centers of ethical digital literacy. Originality -The research contributes new insights by highlighting a rarely explored intersection between Islamic education and digital transformation, thus offering a valuable model for integrating religious values with technological advancement in education.